Monolithic integration of one VCSEL on a single mode fiber - Piccirillo Federica; Zimmer Michael; Giaquinto Martino; Micco Alberto; Jetter Michael; Michler Peter; Cusano Andrea; Portalupi Simone Luca; Ricciardi Armando (Nanophotonics)
The implementation of compact fiber-coupled light sources and devices represents a highly sought through technological goal, in wearable technologies, point-of-care units, telecommunication, and even quantum technology. In particular, a strong reduction of the overall device footprint, still ensuring a compact electrical contacting, would play an important role for electrically driven and electrically controlled devices. Here we show the integration of electrically pumped vertical-cavity surface-emitting lasers on multi-mode and single-mode fibers. The optimized integration technique is enabled by the advanced fiber-to-laser coupling design allowed by a detailed numerical investigation, as well as by an improved technological approach. While for the integration on multimode fibers, an important improvement over state-of-the-art is achieved, the integration on single-mode fiber is here demonstrated for the first time. All experimental results include reproducibility studies to show that the developed technique can be considered for larger scale implementations and are further supported by numerical investigation. This work marks an important step forward in the miniaturization of fiber-based optoelectronics devices which will be highly beneficial for various research and technology developments.